Triarylboron‐Doped Acenethiophenes as Organic Sonosensitizers for Highly Efficient Sonodynamic Therapy with Low Phototoxicity. Issue 49 (7th November 2022) - Liu, Kanglei; Jiang, Zhenqi; Zhao, Fenggui; Wang, Weizhi; Jäkle, Frieder; Wang, Nan; Tang, Xiaoying; Yin, Xiaodong; Chen, Pangkuan
Abstract: The development of efficient organic sonosensitizers is crucial for sonodynamic therapy (SDT) in the field of cancer treatment. Herein, a new strategy for the development of efficient organic sonosensitizers based on triarylboron‐doped acenethiophene scaffolds is presented. The attachment of boron to the linear acenethiophenes lowers the lowest unoccupied molecular orbital (LUMO) energy, resulting in redshifted absorptions and emissions. After encapsulation with the amphiphilic polymer DSPE‐mPEG2000, it is found that the nanostructured BAnTh‐NPs and BTeTh‐NPs (nanoparticles of BAnTh and BTeTh) shows efficient hydroxyl radical ( OH) generation under ultrasound (US) irradiation in aqueous solution with almost no phototoxicity, which can overcome the shortcomings of O2 ‐dependent SDT and avoid the potential cutaneous phototoxicity issue. In vitro and in vivo therapeutic results validate that boron‐doped acenethiophenes as sonosensitizers enable high SDT efficiency with low phototoxicity and good biocompatibility, indicating that boron‐functionalization of acenes is a promising strategy toward organic sonosensitizers for SDT. Abstract : A new strategy of organic sonosensitizers based on boron‐doped acenethiophene scaffolds is presented. Ultrasound irradiation of water‐dispersible nanoparticle BAnTh‐NPs and BTeTh‐NPs can efficiently generate OH while exhibiting low phototoxicity. In vitro and in vivo studies indicate that boron‐doped acenethiophenes exhibit high sonodynamic therapy efficiency with excellent biocompatibility.